CHUVAS INTENSAS EM VOLTA REDONDA - Santos, Hugo Thaner dos; Duarte, Sérgio Nascimento (IRRIGA, 2021)
HEAVY RAINFALL EVENTS IN VOLTA REDONDA HUGO THANER DOS SANTOS1 E SERGIO NASCIMENTO DUARTE2 1Direção de Ensino, Instituto Federal do Rio de Janeiro, Rua José Breves, 550, Centro, 27197-000, Pinheiral, RJ, Brasil. hugo.santos@ifrj.edu.br 2Departamento de Engenharia de Biossistemas, Universidade de São Paulo, Avenida Pádua Dias, 11, São Dimas, 13418-900, Piracicaba, SP, Brasil. snduarte@usp.br 1 ABSTRACT Cities do not implement proper drainage management practices due to lack of planning or of literature on hydrological issues. Volta Redonda fits this context, since it experiences several extreme rainfall events. The aims are to investigate whether the maximum daily rainfall rates have increased in intensity over the years, to adjust the annual maximum daily rainfall events to a probability distribution model and to generate hydrological data to favor the design of surface drainage. Data deriving from a pluviometric station located in the herein assessed county were used in the current study. Mann-Kendell Test and Gumbel distribution were applied to the analyzed series. The most rainfall events recorded values ranging from 60 mm to 80 mm; 95% of the maximum annual daily rainfall events accounted for values lower than 125 mm. Gumbel’s α and β recorded 69.9 and 17.9, respectively. The herein analyzed rainfall series can be considered stationary, although it presented clear upward trend from 1960 to 1999. Results in the current study can be used to help developing drainage systems in Volta Redonda; it is recommended using mean rainfall intensity of 150 mm h-1 for small urban drainage structures, whenever it is not possible estimating runoff concentration time. Keywords: conurbation, extreme events, Gumbel, Southern Rio de Janeiro State. SANTOS, H.T.; DUARTE, S.N. CHUVAS INTENSAS EM VOLTA REDONDA 2 RESUMO As cidades não exercem uma adequada gestão da drenagem, devido à ausência de um planejamento ou falta de bibliografia hidrológica. Volta Redonda enquadra-se nessa situação, apresentando diversos eventos pluviométricos extremos. Os objetivos foram verificar se as chuvas máximas diárias têm aumentado em intensidade ao longo dos anos, ajustar as chuvas diárias máximas anuais a um modelo de distribuição de probabilidades e gerar dados hidrológicos que favoreçam o dimensionamento de sistemas de drenagem superficial. Utilizaram-se dados pluviométricos de um posto da cidade. A essa série foi aplicado o Teste de Mann-Kendell e a distribuição de Gumbel. Os maiores eventos de chuvas intensas apresentaram valores de 60 a 80 mm e 95% dos eventos de chuva máxima diária anual são menores que 125 mm. Os coeficientes α e β de Gumbel são, respectivamente, 69,9 e 17,9. A série pluviométrica pode ser considerada estacionária, embora tenha havido uma franca tendência ascendente de 1960 a 1999. Os resultados obtidos nesse estudo podem ser utilizados na elaboração de sistemas de drenagem de Volta Redonda, sendo recomendado o uso de uma intensidade média de 150 mm h-1 para pequenas estruturas de drenagem urbana, quando não é possível estimar o tempo de concentração do escoamento superficial. Palavras-chave: conurbação, eventos extremos, Gumbel, Sul Fluminense.